2012
DOI: 10.1088/0031-8949/85/04/047001
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘Electromagnetic potentials without gauge transformations’

Abstract: In this comment it is demonstrated that contrary to the claim in the title, ‘Electromagnetic potentials without gauge transformations’, the potentials were actually calculated in the Coulomb gauge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Stewart showed that this representation of the time dependent vector potential satisfies Maxwell equations and even more, that it is equivalent to retarded representation obtained by Jackson [17]. However, its very easy to prove that (34) is in fact the potential (21) coming from the Helmholtz-Maxwell elliptic theorem. We have the following:…”
Section: Theoremmentioning
confidence: 76%
See 2 more Smart Citations
“…Stewart showed that this representation of the time dependent vector potential satisfies Maxwell equations and even more, that it is equivalent to retarded representation obtained by Jackson [17]. However, its very easy to prove that (34) is in fact the potential (21) coming from the Helmholtz-Maxwell elliptic theorem. We have the following:…”
Section: Theoremmentioning
confidence: 76%
“…Corollary to theorem 5: the instantaneous Stewart representation (34) for the vector potential is equivalent to the retarded representation (21). Proof: Using standard vector identities and Green's functions properties we can write down…”
Section: Theoremmentioning
confidence: 94%
See 1 more Smart Citation
“…A result that has been given by Engelhardt and Onoochin using examples. For this reason we cannot believe that in any sense we are trying to refute statements in [2], instead we are offering a possible theoretical explanation of their results. (ii) The proof that the new potentials are gauge invariant quantities.…”
mentioning
confidence: 93%
“…The foregoing is a summary of the conventional wisdom about the widespread method to solve Maxwell's equations by means of the g-potentials, and can be read in any textbook on electromagnetic theory (see, e.g., [1, pp 239-241]). In the critical comment by Engelhardt and Onoochin [2] on the paper [3] it is proved, in the right manner, that the field equations deduced for the introduced gauge invariant potentials ϕ g , A g are formally the same as those for the g-potentials in the Coulomb gauge. However, we believe that this is not a criticism because the authors overlooked the main achievement of [3] that for us relies on two independent points: (i) A general argument for the possibility of different solutions in different gauges unrelated by a gauge transformation.…”
mentioning
confidence: 99%